Perencanaan Sistem Plambing Air Bersih Gedung Rusunawa Mahasiswa Universitas Andalas - Puti Sri Komala; Suarni Saidi Abuzar; Purnama Mentari Dewi (Jurnal Dampak, 2018)
Design of water supply and fire protection system in a low income five storey apartment of Andalas University has been conducted based on Indonesian National Standard (SNI) regulation No.03-7065-2005, that the building which has more than 500 inhabitants or more than 1.500 visitors, should prepare plumbing system design. The University of Andalas Student Rental Building is a residential building of five floors. In this water supply plan the water source is supplied from the Unand’s water treatment plant. The water supply system uses a roof tank system with a combination of gravity flow and booster pump. The water supply tank consists of the bottom tank and the upper tank with capacities of 74 m3 dan 4,5 m3, respectively. The booster pump meets the critical pressure on the 3rd floor up to the 5th floor with 5,44 m head. Class II fire prevention systems use hydrant and sprinkler systems with automatic wet-type upright pipes. The distribution pipes use PVC pipes (1/2  - 1 1/4) inches, while the hydrants and sprinkler pipes use Black Steel (1-4) inch pipe.